2017
DOI: 10.1093/heapol/czw165
|View full text |Cite
|
Sign up to set email alerts
|

Can voluntary pooled procurement reduce the price of antiretroviral drugs? a case study of Efavirenz

Abstract: Voluntary pooled procurement significantly reduced the price of 600 mg generic Efavirenz between 2009 and 2013. Voluntary pooled procurement therefore offers a potentially effective strategy for the reduction in HIV drug prices and the improvement of technical efficiency in HIV programming. Further work is required to establish if these findings hold also for other drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 37 publications
0
17
2
Order By: Relevance
“…Given the high prevalence of hypertension in LMICs, the scale of need is large, affording significant purchasing leverage. Pooling volumes through centralized procurement within one country or regionally between countries, as for example the PAHO strategic fund does for the PAHO region, can lead to price decreases of up to 90% across a range of medications, including cardiovascular treatments [ 21 ].…”
Section: An Ounce Of Preventionmentioning
confidence: 99%
“…Given the high prevalence of hypertension in LMICs, the scale of need is large, affording significant purchasing leverage. Pooling volumes through centralized procurement within one country or regionally between countries, as for example the PAHO strategic fund does for the PAHO region, can lead to price decreases of up to 90% across a range of medications, including cardiovascular treatments [ 21 ].…”
Section: An Ounce Of Preventionmentioning
confidence: 99%
“…Empirically, much of the evidence comes from the health literature and consists of mean price comparisons and qualitative reviews of procurement systems. Contributions analyzing price changes include Kim and Skordis-Worrall (2017), who find pooled procurement by the Global Fund to reduce the price of Efavirenz by 16 to 19 percent in a differences-in-differences analysis of WHO Global price report mechanism (GPRM) data from 2004 to 2013, and Wirtz et al (2009), who find no effect of procurement volume for twelve ARVs using the same data. Seidman and Atun (2017) provide a literature review of thirty-eight papers tracked through PubMed, Embase, CINAHL and the Health Economic Evaluation Database and provide several examples of contributions concluding to cost savings from pooled procurement.…”
Section: Introductionmentioning
confidence: 99%
“…53 Proper management of pooled procurement increases pharmaceutical procurement efficiency and in most cases actually does reduce transaction costs. 52,55 We found that experienced intervention burden and lower opportunity costs related to the previous system influenced the acceptability of the Jazia PVS. The findings of this study are similar to those of an innovative programme which was conducted in Senegal and Vietnam to integrate the medical product supply chain for all public-sector vaccines, drugs, and other health products.…”
Section: Discussionmentioning
confidence: 92%